2020
DOI: 10.1111/ced.14314
|View full text |Cite
|
Sign up to set email alerts
|

Management of nail psoriasis

Abstract: Nail involvement is estimated to affect 80-90% of patients with psoriasis at some point in their lives and is often associated with severe disease. Patients with nail involvement experience pain, functional impairment and social stigma, with significant restriction of daily activities and quality of life. Nail psoriasis is also considered a risk factor for the development of psoriatic arthritis (PsA). Management of nail psoriasis is deemed challenging and as a result, it is often left untreated by physicians. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
0
27
0
4
Order By: Relevance
“…In one study, intramatricial methotrexate administration was found to be more effective in treating nail psoriasis than administration of triamcinolone or cyclosporine, with fewer side effects [ 30 ]. Undoubtedly, a breakthrough in the treatment of nail psoriasis was the use of biological drugs [ 15 , 16 , 31 ]. Biologic therapy including anti-TNF-a, IL-17 and IL-12/23 antibodies used in the treatment of psoriasis and PsA appears to be highly effective in the treatment for nail psoriasis [ 15 , 16 , 31 ] as well as small molecule therapies [ 15 , 16 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In one study, intramatricial methotrexate administration was found to be more effective in treating nail psoriasis than administration of triamcinolone or cyclosporine, with fewer side effects [ 30 ]. Undoubtedly, a breakthrough in the treatment of nail psoriasis was the use of biological drugs [ 15 , 16 , 31 ]. Biologic therapy including anti-TNF-a, IL-17 and IL-12/23 antibodies used in the treatment of psoriasis and PsA appears to be highly effective in the treatment for nail psoriasis [ 15 , 16 , 31 ] as well as small molecule therapies [ 15 , 16 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, a breakthrough in the treatment of nail psoriasis was the use of biological drugs [ 15 , 16 , 31 ]. Biologic therapy including anti-TNF-a, IL-17 and IL-12/23 antibodies used in the treatment of psoriasis and PsA appears to be highly effective in the treatment for nail psoriasis [ 15 , 16 , 31 ] as well as small molecule therapies [ 15 , 16 , 32 ]. In recent studies, also apremilast showed fast and sustained improvement of nail psoriasis [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations